2014
DOI: 10.1515/cclm-2013-0785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical cases in External Quality Assessment Scheme (EQAS) for the urinary sediment

Abstract: Our findings demonstrate that once the correct identification of urinary sediment particles is obtained, most participants are able to associate urinary findings with the respective clinical conditions, thus establishing the correct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The present study reports on all 27 clinical cases; the results on 10 and seven of which have been described in detail in two previous papers [11,22].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The present study reports on all 27 clinical cases; the results on 10 and seven of which have been described in detail in two previous papers [11,22].…”
Section: Discussionmentioning
confidence: 88%
“…Period 2001-2011: The methods and results of the program, which in this period was under the responsibility and guidance of one of us (G.B.F. ), a nephrologist with an expertise in urinary sediment and urinalysis [18][19][20][21][22][23][24][25], has been described in details elsewhere [6,21,22]. In this period, the descriptive identification of particles were evaluated as correct, partially correct, incorrect or no answer and scored accordingly (5, 3, 0, and −2 respectively).…”
Section: Main Features Of the Programmentioning
confidence: 99%
“…We also recruited many expert nephrologists known for their interest in urine sediment examination and teaching. Notably, studies by Secchiero et al, 18 and Fogazzi et al 19,20 from Italy, in which images of urine sediment particles were interpreted by laboratory personnel, reported variable but often excellent percent agreement. In Secchiero et al, 18 the percentages of reviewers who correctly identified isomorphic RBCs, hyaline casts, and granular casts were 84.7%, 89.5% and 74.9%, respectively.…”
Section: Jama Network Open | Nephrologymentioning
confidence: 99%
“…polarised light microscopy, as well as to the use of specific cytological staining. Therefore, it is essential that clinical laboratories should be involved in reliable internal quality control (IQC) programs and external quality assessment (EQA) schemes for both the preanalytical and analytical phase of urinalysis [24][25][26]. The laboratories should be directly connected with international and national societies or working groups such as the European Federation of Laboratory Medicine (EFLM) or the Italian intersocietary SIBioC/SIMeL working group for urinalysis or Italian urinalysis working group (GIAU) [27].…”
Section: Pigmented Castsmentioning
confidence: 99%